Who Pays the Price of Civilization? - San Juan, Eric A. (Columbia Journal of Tax Law, 2018)
Current events appear to challenge preconceptions of civilization. On opposite sides of the ocean, heads of state are associated with “alternative facts,” alleged fratricide, or death squads.[1] Central to the received notions shaken by these developments would be the rule of law. Can rational legality survive apparently aberrant administrations? To address this question, this Article introduces the evolutionary context from which the rule of law arose. To balance inaccuracies of generalization, this Article proceeds with case studies from both America and overseas. As a particular field of compliance (or noncompliance) with the rule of law, the Article focuses on tax law. As U.S. Justice Oliver Wendell Holmes, Jr. opined in a landmark trans-Pacific case, “Taxes are what we pay for civilized society.”[2] The reasons why people do or don’t comply with taxation may offer insight into legal compliance generally. Thus, a case study of tax may have implications for popular adherence to the rule of law.